Predictors of Vancomycin-Resistant Enterococcus spp. Intestinal Carriage among High-Risk Patients in University Hospitals in Serbia - Ana Janjusevic; Ivana Cirkovic; Rajna Minic; Goran Stevanovic; Ivan Soldatovic; Biljana Mihaljevic; Ana Vidovic; Ljiljana Markovic Denic (MDPI AG, 2022)
The predictors of intestinal carriage of vancomycin-resistant Enterococcus spp. (VRE) among high-risk patients in the counties of the Southeast Europe Region are insufficiently investigated, yet they could be of key importance in infection control. The aim of the study was to identify risk factors associated with fecal VRE colonization among high-risk inpatients in university hospitals in Serbia. The study comprised 268 inpatients from three university hospitals. Data on patient demographics and clinical characteristics, length of hospital stay, therapy, and procedures were obtained from medical records. Chi-squared tests and univariate and multivariate logistic regressions were performed. Compared to the hemodialysis departments, stay in the geriatric departments, ICUs, and haemato-oncology departments increased the risk for VRE colonization 7.6, 5.4, and 5.5 times, respectively. Compared to inpatients who were hospitalized 48 h before stool sampling for VRE isolation, inpatients hospitalized 3-7, 8-15, and longer than 16 days before sampling had 5.0-, 4.7-, and 6.6-fold higher risk for VRE colonization, respectively. The use of cephalosporins and fluoroquinolones increased the risk for VRE colonization by 2.2 and 1.9 times, respectively. The age ≥ 65 years increased the risk for VRE colonization 2.3 times. In comparison to the University Clinical Centre of Serbia, the hospital stays at Zemun and Zvezdara University Medical Centres were identified as a protector factors. The obtained results could be valuable in predicting the fecal VRE colonization status at patient admission and consequent implementation of infection control measures targeting at-risk inpatients where VRE screening is not routinely performed.